Pengaruh Penyuluhan Dengan Media Animasi Terhadap Pengetahuan Dan Sikap Tentang Makanan Bergizi, Seimbang Dan Aman Bagi Siswa SD 08 Cilandak Barat Jakarta Selatan Tahun 2017 - Vera Suzana Dewi Haris (Quality : Jurnal Kesehatan, 2018)
Nutrition issues will impact to the declining quality of human resources, hence nutrition education is vital for elementary students as mainly children have high tendency in choosing snacks over homemade foods. Animation media is part of learning media which provides further accessibility in delivering education/guidance on nutrition. The research design is quasi experiment with one group pretest-posttest design. The research subject is fifth grade students of SDN 08, West Cilandak, Sourth Jakarta. The data was analyzed using Wilcoxon test. This research was conducted in August to September 2017. The data analysis results show a discrepancy between the elementary studentsÂ’ knowledge and behavior relating to nutrition prior to and post guidance with animation media (p value = 0.000). The conclusion of this research is knowledge and behavior of elementary students post guidance on nutritional, balanced, and secured foods using animation is improving compared to the previous condition (prior to guidance). Animation media-based guidance has an effect to the elementary studentsÂ’ knowledge and behavior concerning nutritional, balanced, and secured foods. Keywords: Guidance, nutrition, elementary students, education, behavior.